Addressing the Challenges of Vocabulary Instruction: Strategies for Effective Learning at Junior High School in Lubuklinggau - Oktaviani, Ayu; Triyogo, Agus; Hamdan, Hamdan; Wijayati, Sukma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aimed to describe the challenges done by English teachers in Lubuklinggau face in implementing effective vocabulary teaching. This research conducted in qualitative design with descriptive approach. Sample in this research as four English teachers at different junior high school that consist of state and Privat. In collecting the data, the researchers crated online questionnaire through google form and shared to the subject. The result showed Teaching English vocabulary to students presents challenges like lack of resources, motivation, and emotional barriers. Strategies include providing resources, motivating students, managing classroom dynamics, and using interactive exercises, multimedia resources, and differentiated approaches. To effectively teach English vocabulary, educators should utilize real-world examples, customize materials, and create a nurturing learning environment, while also ensuring efficient classroom control and time allocation. Keywords: English, Challenge, Learning, Teacher, Vocabulary